(untitled) (Fiep Bulletin - online, 2020)
Population aging is a worldwide reality, which is occurring rapidly, especially in Brazil. Functional capacity is one of the most important indicators of the health status of the elderly population and can be conceptualized as the ability to maintain the physical and mental functions necessary for the individual to maintain their autonomy and independence. The present study aimed to evaluate the functional capacity in institutionalized elderly. This is a descriptive, cross-sectional and quantitative study conducted with elderly residents of the Porto Seguro and Yeda Lucena LSIEs, located in district IV of Recife - PE, Brazil, in December 2017. For the collection of data related to functional capacity were used the following instruments: Katz Index for ABVDs; Lawton and Brody Scale for IADLs. Of the 35 elderly included in this study, 65.7% (n = 23) were male, the highest prevalence in the 60–70 age group (58.8%; n = 20). Most of the elderly (76.9%; n = 20) had no partner (divorced, widowed, separated or single), had 1 to 4 children (48.1%; n = 13) and were literate (64.0 %; n = 16). The present study characterizes mostly a long-lived population. Regarding functional capacity, most elderly people have independence for all basic activities, are partially dependent on instrumental activities and advanced activities, most activities are no longer performed by the elderly.